Synthesis of Fluorescent Copper Nanomaterials and Detection of Bi3+ - Wu, Rihan; Ai, Jun; Ga, Lu (Frontiers in Chemistry, 2022)
Based on the aggregation induced luminescence of glutathione protected non noble metal copper nanoparticles (GSH- CuNPs), a fluorescence method for the rapid detection of bismuth (Bi3 +) was developed. The fluorescence intensity of GSH-CuNPs solution is good, and the fluorescence can be quenched in the presence of Bi3 +. Based on this principle, a fluorescence mean for the admeasurement of Bi3 + was built. The linear range was 0-100 mmol / L, and the detection limit was 10 mmol / L. The method is simple, rapid and selective, and can be used for the qualitative detection of Bi3 +.